The Standardized Extract of Ziziphus jujuba Fruit (Jujube) Regulates Pro‐inflammatory Cytokine Expression in Cultured Murine Macrophages: Suppression of Lipopolysaccharide‐stimulated NF‐κB Activity. (8th May 2014) - Chen, Jianping; Du, Crystal Y. Q.; Lam, Kelly Y. C.; Zhang, Wendy L.; Lam, Candy T. W.; Yan, Artemis L.; Yao, Ping; Lau, David T. W.; Dong, Tina T. X.; Tsim, Karl W. K.
<x xml:space="preserve">Abstract</x> The fruit of Ziziphus jujuba Mill., known as jujube or Chinese date, is commonly consumed as a health supplement or herbal medicine worldwide. To study the beneficial role of jujube in regulating immune response, we investigated its roles on the expressions of pro‐inflammatory cytokines in cultured macrophages. Application of chemically standardized jujube water extract for 24 h stimulated the transcriptional expression of interleukin (IL)‐1β, IL‐6, and tumor necrosis factor (TNF)‐α in cultured RAW 264.7 macrophages. In contrast, the pretreatment with jujube water extract suppressed the expression of IL‐1β and IL‐6, but not for TNF‐α in lipopolysaccharide (LPS)‐stimulated macrophages. The IL‐1β and IL‐6 cytokines in LPS‐induced macrophages were suppressed by jujube water extract in both mRNA and protein levels. In parallel, the inhibition of jujube water extract on the transcriptional activity of nuclear factor‐kappa B was revealed in LPS‐induced macrophages. These results verified the bidirectional immune‐modulatory roles of jujube by regulating the expressions of pro‐inflammatory cytokines in macrophages. Copyright © 2014 John Wiley & Sons, Ltd.